THE EFFECTIVENESS OF ISLAMIC LITERATURE TEXT MODEL IN READING SKILLS OF THE COVID-19 PANDEMIC TIME - Husin, Ahmad; Wapa, Andi (Consilium: Education and Counseling Journal, 2025)
National Education aims to educate the nation and develop a whole Indonesian man who is balanced, harmonious, in harmony in his life and life as well as physically and mentally healthy. To achieve this goals, education is needed that is very concerned about the needs of students. The students' needs are intended forms of innovative learning media. Literary works (Islamic literary texts) are expected to be used to awaken the public (readers) to return to their nature, on the right path. Literature is an expression of society, therefore the emergence of a literary work is closely related to the problems that arise at that time. In addition, literature can serve as a work of art that can be used to entertain readers. In a novel there must be a variety of expressions, namely the expression or process of stating. In this analysis, there are findings about charting and data codification of focus on religious values that can be applied in the Islamic literary text model in learning reading skills in online learning during the Covid-19 pandemic. The Islamic literary text used is the novel of Api Tauhid by Habiburrahman El Shirazy. The results of the preliminary study indicate that the failure in language learning, especially reading skills, has been caused by the approach used not being focused on efforts to create communicative abilities / skills. Reading skills are carried out through a one-way approach. Students are asked to read the text, do the exercises, and end by discussing the results of student work. Such a model is very irrelevant to the level of interest of students in learning to read. What students need how they become reliable readers. The next, "learning outcome" is to make a product. With regard to reading material, it is found that the reading material has not been designed adequately. This can be seen from the low readability of reading materials. With regard to readers, it appears that reading activities are still low, mastery of language aspects, the ability to identify essay structure, and the ability to understand the content of the reading. This study revealed the following findings: the methods of teaching reading skills was implemented based on mental visualization and association of ideas so as to make language sound natural. This methods were closely related to active, innovative and constructivist method. The methods of teaching reading skills were faster in grasping key points and dominates practice, and is an active method. The recommendations put forward based on these findings are that it becomes a demand for educators to master various teaching models, instill interest in reading literature (Islamic literature) and learning experiences in students as early as possible, and familiarize the teaching-learning process by creating a happy and passionate atmosphere in cultivating. literary works (Islamic literature) as a text model in learning reading skills, especially the application of network-based learning models (online).